2020
DOI: 10.1136/bcr-2020-239218
|View full text |Cite
|
Sign up to set email alerts
|

Guillain-Barré syndrome after COVID-19 in Japan

Abstract: We report the first case of Guillain-Barré syndrome (GBS) associated with SARS-CoV-2 infection in Japan. A 54-year-old woman developed neurological symptoms after SARS-CoV-2 infection. We tested for various antiganglioside antibodies, that had not been investigated in previous cases. The patient was diagnosed with GBS based on neurological and electrophysiological findings; no antiganglioside antibodies were detected. In previous reports, most patients with SARS-CoV-2-infection-related GBS had lower limb predo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 23 publications
0
13
1
9
Order By: Relevance
“…A patient with MFS had mild symptoms and did not receive any treatment [ 12 ]. One patient had an excellent modified Erasmus GBS Outcome Score (mEGOS), and so did not receive treatment [ 13 ]. One more patient was symptomatically treated with acetaminophen and had a complete recovery [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…A patient with MFS had mild symptoms and did not receive any treatment [ 12 ]. One patient had an excellent modified Erasmus GBS Outcome Score (mEGOS), and so did not receive treatment [ 13 ]. One more patient was symptomatically treated with acetaminophen and had a complete recovery [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…After thorough literature review, we found a substantial number of reported cases and case series of Covid-19 infection presented with GBS. Table 1 summarizes demographic, type of relationship with Covid-19, clinical and GBS sub-types, response to specific GBS treatment, and outcome of different GBS cases who presented in concurrent with Covid 19 infection [[ [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] ],[ [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] ...…”
Section: Discussionmentioning
confidence: 99%
“…Common neurological symptoms of COVID-19 are headache, dizziness, dysgeusia/ageusia, hyposmia/anosmia, seizure, stroke, and encephalopathy [ 2 ]. There have been reported cases of Guillain-Barré Syndrome (GBS) associated with COVID-19 from different parts of the world [[ [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] ],[ [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] ,…”
Section: Introductionmentioning
confidence: 99%
“…As in GBS associated with Zika virus infection, electrophysiological features of GBS associated with COVID‐19 are usually suggestive of demyelination compatible with those of AIDP 34–36 . However, some patients with AMAN or acute motor sensory axonal neuropathy have also been reported 13,34,36,37 . According to a systematic literature review from January to June 2020, the mean interval between the onset of COVID‐19 and GBS symptoms was 11.5 days 35 .…”
Section: Introductionmentioning
confidence: 99%